The Implementation of Learning Tourism Models to Nurture Environment Care Behavior - Sujarwo Sujarwo; Ibnu Samsi; Lutfi Wibawa (Jurnal Cakrawala Pendidikan, 2018)
Abstract: The study tour learning model was an outside school learning activity which was organized by lecturers, students and alumni of Non-Formal Education Study Program,  Faculty of Educational Sciences, Universitas Negeri Yogyakarta as a part of practice activity. This activity was conducted at Gembira Loka Zoo,Yogyakarta. This research aims at implementing the study-tour learning model to nurture the environmental care behaviour through outside learning program. This study can be categorized as action research. The subject of this research was the kindergarten students who visited Gembiraloka zoo. The data were collected through observation and interview, and those were analyzed descriptively. The results showed the followings: (1) the study-tour learning model was conducted through outdoor school activities which involved the following steps: socialization, core activities; welcoming, conditioning, creative corner, zoos or flora tour , reflection and closing; (2) the environmental care behaviors through the activity were friendly, respect, clean environment awareness, compassion on animals and plants, polite, and making good friends.Keywords :study-tour learning model, outside learning, environmental care behavior IMPLEMENTASI MODEL WISATA BELAJAR UNTUK MENUMBUHKAN PERILAKU PEDULI LINGKUNGAN Abstrak: Model wisata belajar dilakukan melalui praktik pembelajaran luar sekolah. Pembelajaran luar sekolah dilakukan di kebun binatang Gembiraloka oleh tim pemandu dan pendamping mahasiswa PLS FIP UNY sebagai bagian dari kegiatan praktik pembelajaran. Penelitian ini bertujuan untuk mengimplementasikan model wisata belajar untuk menumbuhkan sikap peduli pada lingkungan melalui program pembelajaran luar sekolah di kebun binatang. Penelitian ini merupakan jenis penelitian tindakan sebagai implementasi hasil pengembangan model. Subjek penelitian ini adalah peserta wisata belajar anak-anak taman kanak-kanak  di kebun binatang Gembiraloka. Data dikumpulkan dengan metode observasi dan wawancara serta dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan: (1) model wisata belajar dilakukan melalui pembelajaran luar sekolah dengan tahapan sosialisasi program wisata belajar di dinas pendidikan kota/kabupaten, kegiatan inti, penyambutan, bina suasana, pojok kreatif, tour to zoo or flora, reflektif, dan penutup; (2)   perilaku peduli lingkungan  yang berhasil  ditumbuhkan meliputi  ramah dan menghargai sesama, sadar bersih lingkungan, menyayangi binatang, menyayangi tumbuhan, bersikap santun, dan mampu berteman dengan baik.Kata kunci: model wisata belajar, pembelajaran luar sekolah, perilaku peduli lingkungan